Mediterranean diet during pregnancy and infant neurodevelopment: A prospective birth cohort study - Dai, Fei-cai; Wang, Peng; Li, Qiong; Zhang, Lei; Yu, Li-jun; Wu, Lin; Tao, Rui-xue; Zhu, Peng (Frontiers in Nutrition, 2023)
Abstract Background: Embryonic neural development is associated with intrauterine nutritional status. However, few cohort studies estimate the relationship between maternal dietary patterns during pregnancy and offspring's early neurodevelopment. Objective: To examine the impact of the Mediterranean diet (MD) during pregnancy on infant neurodevelopment, including the potential mediating role of cord blood metabolites. Methods: Among 1471 mother-child pairs in a prospective birth cohort study in Hefei, China, we investigated associations between maternal MD score [calculated based on a validated food frequency questionnaire (FFQ)] and child neurodevelopment at infancy [assessed using Ages and Stages Questionnaires, Third Edition (ASQ-3)]. Cord blood metabolic markers (including C-peptide, , high-density lipoprotein-cholesterol, low-density lipoprotein-cholesterol, total cholesterol and triglycerides) were measured. Results: The MD score was negatively associated with communication domain developmental delays in infants [relative risk (RR) with 95% CI: 0.34 (0.16, 0.72)]. Compared with girls, boys born from mothers with lower MD scores during pregnancy were inclined to the failure of the communication domain [RRs with 95% CI for boys: 0.34 (0.14, 0.84); for girls: 0.26 (0.06, 1.18)]. Mediation analysis showed that the association in boys between maternal MD score and failure of communication domain mediated by C-peptide was 19.4% but not in girls. Conclusions: Adhering to the MD during pregnancy was associated with a decreased risk of poor neurodevelopment, possibly mediated by lower levels of cord blood C-peptide.